COMPARITIVE STUDY ON THE EFFECT OF RHOZOBIUM INOCULUM ON IMBEDDED SEEDS AND GERMINATED SEEDS OF VIGNO MUNGO L. - Pria, S; Shanmugapriya, O.N. (JOURNAL OF ADVANCES IN NATURAL SCIENCES, 2014)
The Rhizobium was isolated from the plant root and purified. The isolated rhizobium sample was identified based on morphological and bio chemical characterization. The result of biochemical tests showed positive result in indole test, citrate utilization test,starch hydrolysis test, urea hydrolysis test and catalase test. The isolated culture was mass multiplied and used by seed treatment like imbibed treatment and germinated treatment. After treatment the seedlings per planted separately by part culture method. The result showed that the rhizobium inoculation on the emerging radicals of one day old seedling is highly effective in nodulation and biomass production respectively